Résilience et pastoralisme de montagne en France - Laurent, Marie (Nuove Geografie. Strumenti di lavoro, 2022)
In France, mountain pastoralism plays a non-neglectable role in the production of quality products, the dynamism, the cultural identity and the management of the mountainous areas. However, some economic, political and environmental pressures are today challenging this activity. This leads some citizens and consumers of pastoral products as well as public policy makers to question the final products and the ecosystem services that derive from pastoralism as well as the economic and ecological costs associated with predation. At the same time, this extensive breeding activity suffers from the consequences of climate change with droughts and vegetation shifts. This study aims at exploring the resilience and socio ecological system literature to put the pastoral activities in perspective and determine if they possess some resilience characteristics. Through the lense of the 9 attributes of resilience of a framework developed by the Resilience Alliance researchers, this work analyses a literature review, some participant observations performed during an internship at the French Agence National de la Cohésion des Territoires and personal interviews. The conclusions are that the socio ecological system of mountain pastoralism in France has most of the characteristics of resilience. This theoretical framework also offers new analyses notably for the social interactions in the summer pasture areas. However, when it comes to predation, this framework gives limited academical perspectives. This is in great part due to the nonconsensual viewpoints of the different stakeholders. It follows that the resilience of the current state of the system is in some places non-desirable since it neglects some of its components. On more consensual matters, such as the adaptation to climate changes, the frameworks applies more easily and sheds light on relevant points.